Bahasa Inggris - Rahmawati, Wuri; Haryanti, Dwi; Laila, Malikatul (LP2M IAIN Sultan Amai Gorontalo, 2022)
This study covers the pragmatics equivalence and violation maxims in the Divergent novel. Classifying the forms of Grice maxim violations and describing the pragmatic equivalence of violation maxims in the Divergent novel are the objectives of this study. It is a qualitative paper that examines violation maxims and pragmatic equivalence in the novel Divergent. The data were direct-utterances infraction maxims in English and Indonesian. There are two types of data analysis techniques employed in this study. The analysis began with a document review, followed by an evaluation of the translation's quality based on pragmatic equivalence. As a result of the research, the following findings were discovered: 139 data were classified as violation maxims. The majority of the results (45,32.4%) involved violations of the quality standard. Second, based on the qualitative parameter of pragmatic equivalence, a total of 137 out of 139 data points were deemed